2023
DOI: 10.1177/17470218231155738
|View full text |Cite
|
Sign up to set email alerts
|

Identifying unfamiliar voices: Examining the system variables of sample duration and parade size

Abstract: Voice identification parades can be unreliable due to the error-prone nature of earwitness responses. UK government guidelines recommend that voice parades should have nine voices, each played for 60 seconds. This makes parades resource-consuming to construct. In the present paper we conducted two experiments to see if voice parade procedures could be simplified. In Experiment 1 (N=271, 135F), we investigated if reducing the duration of the voice samples on a nine-voice parade would negatively affect identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(25 citation statements)
references
References 77 publications
(175 reference statements)
9
16
0
Order By: Relevance
“…Although the Home Office recommend that voice samples should be 60s, Pautz et al (2023) showed that there was no difference in performance between 15 s and 60 s samples, thus for the present research, excerpts featuring the interviewees were spliced together to produce a 15 s sample for each speaker. The voice samples were all taken from different sections of each interview so that the content of speech differed across speakers.…”
Section: Voice Parade Materialsmentioning
confidence: 93%
See 4 more Smart Citations
“…Although the Home Office recommend that voice samples should be 60s, Pautz et al (2023) showed that there was no difference in performance between 15 s and 60 s samples, thus for the present research, excerpts featuring the interviewees were spliced together to produce a 15 s sample for each speaker. The voice samples were all taken from different sections of each interview so that the content of speech differed across speakers.…”
Section: Voice Parade Materialsmentioning
confidence: 93%
“…A total of N = 180 participants were recruited via the online recruitment platform Prolific.co. The sample size, per condition, is either similar to or exceeds contemporary studies in the area (Kerstholt et al, 2006;Pautz et al, 2023;Perfect et al, 2002;Philippon et al, 2013;Smith et al, 2020). The present research, like most voice identification research, was constrained by the cost of participant recruitment.…”
Section: Participantsmentioning
confidence: 94%
See 3 more Smart Citations